PDF Cavity Disinfection Using Er,Cr:YSGG Laser Induced Photoacoustic Streaming Technique: Rand kareem Jassim Hussein Ali Jawad* - Kareem, Rand (Iraqi Journal of Laser, 2022)
Abstract: Aim: The goal of this research was to study the influence of Er,Cr:YSGG laser at short pulse duration (60 µsec) on the number of streptococcus mutans bacteria in vitro.Material and Methods:  twenty-eight extracted third molars free of caries, cracks, and other irregularities were used. For the testing of the materials, both the agar well technique and a tooth cavity model were employed. The agar wells of plates that had been inoculated with Streptococcus mutans previously were stuffed with the test materials, in order to conduct the tests. The zones of inhibition were assessed using millimeter measurements, after an incubation period of 48 hours .In order to accomplish the tooth cavity model test, cylindrical cavities were invented in the occlusal surface of the teeth, which was kept even. The teeth were stored for 72 hours at 37°C in a broth culture of Streptococcus mutans. Following this, the teeth were divided arbitrarily into four groups of seven teeth (each including 14 cavity preparations). The experimental cavities in the first group (A) were not treated and considered as a control. In group B, a cavity disinfectant based on chlorhexidine was applied to the experimental cavities for 60 seconds. In group C, an erbium, chromium doped yttrium scandium gallium garnet laser was used at a short pulse duration (60 µsec) (0.25 watts, 15 Hz, 1% air, 1% water). In the last group, a chlorhexidine cavity disinfectant was applied for 60 seconds, followed by a laser treatment for 30 seconds with the same parameters as those described previously. The teeth were stored in saline for a period of three days. Standard amounts of dentin chips were retrieved from the cavity walls. ANOVA test was used to analyze repeated measure mean between tested concentration and control. Data expressed as mean ±SE.  LSD tests was used to calculate the significant differences between tested mean.Result: After the statistical test, the highly significant difference in the diameter of inhibition zone was observed in group D (26 mm) where both chlorhexidine and laser were used followed by group B (18.71 mm) where the chlorhexidine gluconate based cavity disinfectant used alone, the least significant difference observed in group C (10.26mm) where the laser used alone.Conclusion: According to this in vitro study, a photon-induced photoacoustic streaming technique using an Er,Cr:YSGG pulse laser at short pulse duration effectively agitates a chlorhexidine-based cavity disinfectant, which leads to the inhibition of Sterptococcus Mutans.